A computational study of adsorption and vibrations of UF6 on graphene derivatives: Conditions for 2D enrichment. (January 2015) - Koh, Yang Wei; Westerman, Kenneth; Manzhos, Sergei
Abstract: We present an ab initio study of UF6 adsorption and vibrations on graphene derivatives: pristine single and double layer graphene, as well as (single layer) hydrogenated and fluorinated graphene. As the substrate results in a range of bonding strengths, from chemisorption to physisorption, both GGA density functional theory (DFT) and dispersion-corrected DFT (DFT-D) are used. The lowest adsorption energy, Eads, is of the order of 1.3/1.6 eV on single layer graphene, 1.2/1.5 eV on double layer graphene, 1.1/1.4 eV on graphane, and 0.1/0.3 eV on fluorographene, with DFT/DFT-D, showing that Eads can be tuned in a wide range by the choice of the substrate. The isotopic splitting in the vibrational spectrum of UF6 observed in vacuum is largely preserved in the adsorbed molecules. The existence of several adsorption configurations with competing Eads leads to overlaps in the vibrational spectra of isotopomers, but isotopomer-unique modes exist on all four surfaces. It may therefore be possible to cause desorption of a selected isotopomer by laser radiation, leading to isotopic separation between the surface and the gas.